Improving 2100 MHz Cellular Connectivity in Wonokerso, Sragen: Comprehensive Insights from MIMO Antenna Variation Analysis - Muzzaki, Muhammad Raihan; Ayudya, Dila Ayudya; Afifah, Dinda Roshmalia Nur; Pinem, Ebeneser; Syahbana, Egia M.; Alfin Hikmaturokhman; Putri , Hasanah (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
This research discusses 4G-LTE cellular network coverage planning in Wonokerso, Sragen, Central Java, at the 2100MHz frequency by comparing MU-MIMO and SU-MIMO. The growing demand for connectivity is driving a thoughtfulapproach to network development. MU-MIMO uses multiple antennas to increase throughput, while SU-MIMO relieson one antenna per user. The analysis results show that the average signal level (coverage by signal level) for SUMIMO and MU-MIMO in signal strength is -87.88 dBm and -87.77 dBm, respectively. The standard deviation for SUMIMO and MU-MIMO is 9.84 dBm and 14.34 dBm, respectively. In the effective SU-MIMO and MU-MIMO signals, the signal strength gets the same value of -119.36 dBm. The standard deviation for SU-MIMO and MU-MIMO is 7.3 dBmand 7.28 dBm, respectively. On average, the C/(I+N) SU-MIMO and MU-MIMO ratios for signal strength get values of7.75 dB and 7.41 dB, respectively. The standard deviation for SU-MIMO and MU-MIMO is 5.5 dB and 5.15 dB,respectively. And for SU-MIMO and MU-MIMO signal throughput, the signal strength gets a value of 30,455.75 kbpsand 24,731.04 kbps, respectively. The standard deviation for SU-MIMO and MU-MIMO is 28,192.34 kbps and 17,057.9kbps, respectively. Overall, SU-MIMO tends to provide lower but more consistent signal levels, whereas MU-MIMOexhibits a slightly higher average signal level with greater variation